ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL OPERASI PECAHAN DITINJAU DARI GAYA BELAJAR - Rihana Rihana; Sumarni Sumarni; Mohamad Riyadi (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
This study aims to: (1) find out the learning styles of students, (2) find out the difficulties experienced by students in solving fractional operations problems. This type of research is a descriptive qualitative research. The subjects of this study were seventh grade students of SMP Mubarokul Ulum with a total of 22 students who had received fractions material. The data collection procedure begins with filling out a learning style questionnaire. After getting the data on student work, two students with visual learning styles were selected, two students with auditory learning styles and two students with kinesthetic learning styles to be tested, interviewed and documented. The results showed that: (1) out of 22 students, two students had a visual learning style, eight students had an auditory learning style, 10 students had a kinesthetic learning style and there was a discovery of a new learning style, namely a blend of Visual-Kinesthetic learning styles totaling one student. and Auditorial-Kinesthetic learning style amounted to one student. (2) The difficulties experienced by the first subject with the type of visual learning style tend to be difficult in using concepts and the second subject tends to have difficulty in solving verbal problems. The third and fourth subjects who have an auditory learning style tend to have difficulty in solving verbal problems and the fifth subject with a kinesthetic learning style type that tends to have difficulty using concepts while the sixth subject tends to have difficulty using principles